Compound impact of land use and extreme climate on the 2020 fire record of the Brazilian Pantanal. Issue 10 (7th July 2022) - Ferreira Barbosa, Maria Lucia; Haddad, Isadora; da Silva Nascimento, Ana Lucia; Máximo da Silva, Gabriel; Moura da Veiga, Renata; Hoffmann, Tânia Beatriz; Rosane de Souza, Anielli; Dalagnol, Ricardo; Susin Streher, Annia; Souza Pereira, Francisca R.; Oliveira e Cruz de Aragão, Luiz Eduardo; Oighenstein Anderson, Liana
Abstract: Aim: Our aim was to quantify the influence of climate and land use on major fires that occurred during the 2020 drought over the Brazilian Pantanal region. Location: Alto Paraguay Basin, central‐western flank of Brazil. Time period: 2003–2020. Methods: We calculated climatic and burned area anomalies and Spearman's correlation between precipitation and sea surface temperature (SST). We assessed water coverage to identify the impact of the 2020 drought. We produced fire recurrence maps, identified the areas that burned for the first time in 2020, and estimated the carbon loss. Lastly, we assessed the burned areas within land‐use classes and land tenure. Results: The anomalies showed that climatic variables in 2020 had an atypical behaviour, being hotter and drier than the historical average. The water surface area in the Pantanal has been decreasing annually from 2003, and in 2020 the reduction was 34% greater than the annual average. Burned areas in 2020 were 200% greater than the long‐term average, and 35% of the burned areas occurred for the first time in this year. We showed that 84% of these new fires occurred within natural vegetation, with 39% of the burned areas occurring in forests, an increase of 514%. Forest fires were responsible for 47% of the carbon loss in 2020. Finally, 70% of the fires in 2020 occurred within rural properties, 5% in indigenous lands and 10% in protected areas. Main conclusions: The unprecedented fires in 2020 were not only a result of atypical climate, but also a consequence of the intensification of fire‐related human activities. Rural properties play a major role in Pantanal fires, requiring law enforcement and a consistent plan for increasing the protection of the conservation areas. We argue that ineffective fire prevention and the lack of suppression strategies were also key in enhancing the magnitude of these fires.